2019
DOI: 10.1002/anie.201905186
|View full text |Cite
|
Sign up to set email alerts
|

White‐Light Emission from Dual‐Way Photon Energy Conversion in a Dye‐Encapsulated Metal–Organic Framework

Abstract: The design of white‐light phosphors is attractive in solid‐state lighting (SSL) and related fields. A new strategy in obtaining white light emission (WLE) from dual‐way photon energy conversion in a series of dye@MOF (LIFM‐WZ‐6) systems is presented. Besides the traditional UV‐excited one‐photon absorption (OPA) pathway, white‐light modulation can also be gained from the combination of NIR‐excited green and red emissions of MOF backbone and encapsulated dyes via two‐photon absorption (TPA) pathway. As a result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
79
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(79 citation statements)
references
References 39 publications
(43 reference statements)
0
79
0
Order By: Relevance
“…The longer lifetime for the RhB@DUT‐52 composites further demonstrates the existence of resonance energy transfer from DUT‐52 to RhB. For the composites, the decreased lifetime from R@D1 to R@D3 reveals that the energy transfer in RhB@DUT‐52 becomes more efficient with the increasing content of RhB from 0.89 to 4.0 % . Besides, a fluorescence titration experiment showed that the fluorescence intensity of DUT‐52 was obviously quenched when adding RhB aqueous solution to its suspension, which also indicates the energy‐transfer process between DUT‐52 and RhB (Figure S8, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The longer lifetime for the RhB@DUT‐52 composites further demonstrates the existence of resonance energy transfer from DUT‐52 to RhB. For the composites, the decreased lifetime from R@D1 to R@D3 reveals that the energy transfer in RhB@DUT‐52 becomes more efficient with the increasing content of RhB from 0.89 to 4.0 % . Besides, a fluorescence titration experiment showed that the fluorescence intensity of DUT‐52 was obviously quenched when adding RhB aqueous solution to its suspension, which also indicates the energy‐transfer process between DUT‐52 and RhB (Figure S8, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Hence, it is easyt of ind that the blue emission of the composites is based on MOF DUT-52 and the red emission is based on RhB molecules. [38] Besides,afluorescence titration experiment showed that the fluorescence intensity of DUT-52 was obviously quenched when adding RhB aqueous solution to its suspension,w hich also indicates the energy-transfer process between DUT-52a nd RhB ( Figure S8, Supporting Information). In addition, the red emission of the composites from R@D1 to R@D3 occurred with ap artial redshift (from 595 to 607 nm), which may be due to the enhanced interactions between RhB molecules with the increasing loading quantity.A ss hown in Figure 2b,a significant spectralo verlap between thea bsorption of RhB and emission of DUT-52 is observed, which illustrates the occurrence of resonance energy transfer from DUT-52 to RhB.…”
Section: Luminescence Properties Of Rhb@dut-52 Compositesmentioning
confidence: 99%
“…[6][7][8][9][10][11] As a kind of porous crystalline hybrid material, metalorganic frameworks (MOFs) [12][13][14][15] are constructed by the coordination of metal nodes (clusters) with organic linkers and are supposed to be promising candidates to exploit optical properties including NLO behaviour, upconversion luminescence, lasing and so on. [16][17][18][19][20] A few cases of powder MOFs have been realized to investigate the third-order NLO properties. [21][22][23] However, such powder MOFs have large scattering and are usually required to be dispersed in solvents for investigating the third-order NLO properties.…”
Section: Introductionmentioning
confidence: 99%
“…[30][31][32] Hence, MOFs with a pore connement effect (with the pore size matching well with the size of organic uorophores) are the most suitable candidates for minimizing the ACQ of uorophores. [33][34][35][36] Chiral MOFs have been recently emerging as potential hosts for chiral synthesis, 37 separation 38,39 and transcription. 40 A recent case based on MOFs showed that the g lum value was increased from 10 À4 to 10 À3 and simultaneously the f lum enhanced from 0.3 to 0.4 by reorganizing a chiral luminescent binaphthyldiamine-imidazole based emitter on the skeleton of a zeolitic imidazolate framework, 41 indicating that MOFs can be candidates for CPL materials.…”
Section: Introductionmentioning
confidence: 99%